Three-dimensional analysis of medium-frequency induction heating of steel pipes subject to motion factor. (October 2016) - Han, Yi; Yu, En-Lin; Zhao, Tian-Xu
Highlights: Dynamic simulation of medium-frequency heat treatment process for pipe was achieved. The steady-state temperature field formed at the weld is "double ellipsoid" shaped. Existence of such hysteresis is the immediate cause of the temperature field. The maximum temperature of the weld inside surface lags behind that of the outside. Abstract: As hydrocarbon resource exploration will extend towards deep sea and alpine cold areas in future, the corresponding welded pipes for oilfield use will face increasingly adverse operating environment. Acquisition of more precise heat source for medium-frequency heat treatment of welded pipes is fundamental to postweld residual stress analysis, weld microstructure improvement and performance research. However, as a pipe billet is subjected to movement factor, it is very tough to solve for a three-dimensional heat source closer to real pattern with complex process parameters. In this paper, the authors utilized a computing method of sequential coupling combining electromagnetic-thermal coupling and relative motion between steel pipe and coils, and designed the corresponding computation flowchart, and by computing pipe billet heat treatment process, they found that the steady-state temperature field formed around a weld appears double ellipsoidal. Further analysis shows that the root cause of the double ellipsoidal temperature field is asymmetric distribution of magnetic flux density and induction current, generated in the weld zone due to electromagnetic effect, within the steel pipe in axial direction. Moreover, stability and hysteresis of pipe billet temperature field were studied. It's found that there is a certain hysteresis between the maximum temperature of inner surface and that of outer surface, because of two different heat sources undergone by the inner and outer surfaces of the weld, as well as relative motion between induction coil and welded pipe. The unique heat transfer process and temperature distribution pattern in wall-thickness direction is the immediate cause of the double ellipsoidal three-dimensional temperature field. This study offers a referenceable analysis method for further exploring steel pipe induction heating process under complex process parameters and optimization of the process parameters.